2010
DOI: 10.1039/b915450g
|View full text |Cite
|
Sign up to set email alerts
|

DIBAL-H mediated triple and quadruple debenzylations of perbenzylated cyclodextrins

Abstract: Diisobutylaluminium hydride (DIBAL-H) mediated reductive removal of benzyl groups was investigated for perbenzylated alpha-, beta- and gamma-cyclodextrins using DIBAL-H in hexane as the reagent. It was found that under the new conditions, the debenzylation can be better controlled to provide sequentially tri- and tetra-debenzylated products in moderate yields and in a regioselective manner. In the case of alpha-cyclodextrin, the removal of the third and fourth benzyl groups took a different path involving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The residue was subjected to silica gel flash chromatography in a solvent gradient of heptane‐EtOAc 1:0→3 : 1→1 : 1→0 : 1 gave tetrol 6 (0.45 g, 60 %) as a clear syrup. NMR showed it identical to the compound reported by Lings group [13,14] …”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…The residue was subjected to silica gel flash chromatography in a solvent gradient of heptane‐EtOAc 1:0→3 : 1→1 : 1→0 : 1 gave tetrol 6 (0.45 g, 60 %) as a clear syrup. NMR showed it identical to the compound reported by Lings group [13,14] …”
Section: Methodssupporting
confidence: 80%
“… [13] These debenzylations are interesting in that removal of secondary benzyl groups occurs and with a degree of selectivity for the already modified A,D glucose‐residues. It is also interesting that secondary debenzylation is not observed in the similar reaction with β‐cyclodextrin [14] …”
Section: Introductionmentioning
confidence: 99%
“…By mesylation of the primary positions followed by reduction with lithium aluminium hydride, different 6-deoxy cyclodextrines were prepared. 43 Deoxygenation of C-6 of benzyl β-lactoside was accomplished by reduction with sodium borohydride of a mesylated precursor. 44…”
Section: Deoxygenation Methodsmentioning
confidence: 99%
“…For example, in the cases of α/β CDs, only benzyl group(s) attached to O6 positions of the A and D units (see Scheme for labeling of a CD) are affected. We later found that this methodology could also be used to synthesize triply and quadruply O‐debenzylated products in gram quantities 4b,c. A downside of the methodology is that a large excess (>30 equiv) of DIBAL‐H is required.…”
Section: Methodsmentioning
confidence: 99%